Sudden emergence of fishery and some aspects of biology and population dynamics of Aluterus monoceros (Linnaeus, 1758) at Veraval - Ghosh, Shubhadeep; Thangavelu, R.; Mohammed, Gulshad; Dhokia, H. K.; Zala, M. S.; Savaria, Y. D.; Polara, J. P.; Ladani, A. A. (Indian Journal of Fisheries, 2011)
The sudden emergence of a fishery and selected aspects of biology and population dynamics of Aluterus monoceros landedby trawlers at Veraval was studied from January 2008 to December 2009. Total catch of 475 t recorded in September 2009,which increased to 7042 t in October dominated in the trawl landings with a contribution of 29.5%. However, in Novemberand December, the catch decreased sharply to 1374 t and 94 t, respectively. The combined length-weight relationship waslog W = -1.50 + 2.694 log L (r = 0.86) (n = 222) indicating allometric growth. Sex ratio was 1:1.05 (n = 129). Femalesattained sexual maturity at 50.2 cm total length. Zoobenthos, dominated by benthic invertebrates, cnidarians and worms,zooplankton dominated by copepods and nekton dominated by Acetes spp. and clupeid juveniles were the major food itemsof A. monoceros. The von Bertalanffy growth equation was Lt = 63.53 [1 – e - 0.22 (t + 0.077)]. Natural mortality, fishing mortalityand exploitation ratio were 0.53, 0.58 and 0.52 respectively.